Monitoring Perkinsus olseni Infection in Manila Clam Ruditapes philippinarum on Intertidal Beachs in Jeju Island - Jeong-Hwa, K.; Thatchaneshkanth, S.; Kajino, N.; Jong-Seop, S.; Kwang-Sik, C. (Korean Society of Malacology, 2024)
Previous studies have shown that the apicomplexan protist Perkinsus olseni induces both sublethal and lethal effects on the Manila clam (Ruditapes philippinarum) along the west and south coasts of Korea, including Jeju Island. In this study, we assessed the prevalence and infection intensity of P. olseni in Manila clams from sand beaches on Jeju Island in July 2022, using Ray's fluid thioglycollate medium assay (RFTM) and histology. Condition index (CI) as the proxy of the fitness of clams (i.e., the ratio of dry or wet tissue weight to the shell weight) collected in July 2022 ranged from 74.5 (Jongdal-ri) to 122.9 (Segwipo), or 0.27 (Moseulpo) to 0.62 (Segwipo). The mean infection intensity, measured as P. olseni cells per gram of gill tissue in clams collected from six sites, ranged from 0 (Geumneung, Gimnyeong, and Moseulpo) to 56,000 cells/g of gills (Seongsan), with prevalence rates (i.e., the percentage of infected clams) ranging from 0 to 47%. Similarly, infection intensity in total tissue ranged from 0 (Geumneung and Gimnyeong) to 47,870 cells/g of tissue (Seongsan), with prevalence rates between 0 and 83%. Histological analysis corroborated these findings, revealing low infection intensity, with infection scores ranging from 0 to 1.0 across the six sites. Despite rising sea surface temperatures in Jeju Island over recent decades due to global warming, P. olseni infection prevalence and intensity appear to have remained stable. The low density of Manila clams in Jeju Island may partially explain the observed low infection intensity and prevalence.
Keywords: Perkinsus olseni; Ruditapes philippinarum; Jeju Island; Infection intensity; RFTM assay; Histology